Multiple site inflammation and acute kidney injury in crush syndrome - Miyauchi, Hiroaki; Okubo, Koshu; Iida, Kiriko; Kawakami, Hiroshi; Takayama, Kentaro; Hayashi, Yoshio; Haruta, Junji; Sasaki, Junichi; Hayashi, Kaori; Hirahashi, Junichi (Frontiers in Pharmacology, 2024)
Crush syndrome, which frequently occurs in earthquake disasters, often leads to rhabdomyolysis induced acute kidney injury (RIAKI). Recent findings indicate that systemic inflammatory response syndrome (SIRS) exacerbates muscle collapse, contributing to RIAKI. The purpose of this study is to investigate the involvement of multiple site inflammation, including intraperitoneal, in crush syndrome. In a mouse model of RIAKI, elevated levels of inflammatory mediators such as TNFα, IL-6, myoglobin, and dsDNA were observed in serum and the peritoneal cavity, peaking earlier in the intraperitoneal cavity than in serum or urine. Our previously developed novel peptide inhibiting leukocyte extracellular traps was administered intraperitoneally and blocked all of these mediators in the intraperitoneal cavity and serum, ameliorating muscle damage and consequent RIAKI. Although further studies are needed to determine whether intraperitoneal inflammation associated with muscle collapse can lead to systemic inflammation, resulting in more severe and prolonged muscle damage and renal injury, early suppression of multiple site inflammation, including intraperitoneal, might be an effective therapeutic target.